Leveraging resource management and duality theories to strengthen circular economy practices in the waste‐to‐energy industry - Tiara, Adhya Rare; Tjahjono, Benny; Beltran, Macarena; Rayns, Francis; Longhurst, Philip J. (Wiley, 2025)
With the immediate actions required to address environmental issues posed by waste generation and the growing interest in the circular economy, anaerobic digestion (AD) offers a promising solution. As a major component of waste‐to‐energy, AD plays a dual role by processing waste and generating renewable energy at the same time, thus contributing to the success of closed‐loop systems. However, the success of AD as a business remains uncertain due to the high costs of material handling. Through a systematic literature review (SLR), this study reveals AD‐specific key barriers in feedstock exchanges and typical strategies applied to address them. The dual role of AD and the involvement of different stakeholders in the upstream processes further complicate these challenges, thus necessitating a more holistic approach to strategy formulation—an aspect not fully covered in the current literature. These gaps present opportunities to theorise the unique operations of AD businesses and the dynamics of multi‐stakeholders in complex feedstock supply processes. This study integrates resource management theories and duality theory, proposing a theoretical framework to enhance the sustainability and circularity of AD ventures. The proposed framework views AD from a resource‐oriented perspective and thus reinforces its pivotal role in fostering a truly closed‐loop system within the circular economy.
Keywords: anaerobic digestion; circular economy; duality theory; resource management; sustainable business; waste-to-energy; 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; Business & Management; 3501 Accounting, auditing and accountability; 3502 Banking, finance and investment